Projeto Vencedor do Prêmio de Mérito Extensionista Maria Filina 2023 - Caniçali Primo, Candida; Silva Castelar Costa, Maysa; Barros Pontes, Mônica; Rabelo Laignier , Mariana; Nascimento Borges, Isabela; Lage Rodrigues, Jaynni; Biasuti Rassele, Lais; de Souza Almeida, Alyne; Oliveira Brunelli , Nathália; Santos Bredoff, Rafaela; Zanetti Resende, Fabíola; Almeida Lima, Eliane de Fátima (Revista Guará, 2023)
-